«ИННОВАЦИЯЛАР ДИФФУЗИЯСЫ, БІЛІМ АҒЫНЫ ЖӘНЕ ЭКОНОМИКАЛЫҚ ӨСУ» ТЕОРИЯЛЫҚ ЖӘНЕ ЭМПИРИКАЛЫҚ МОДЕЛЬДЕРІН ТАЛДАУ - L. S. Spankulova; D. R. Korgasbekov (Экономика: стратегия и практика)
The article is devoted to a review of theoretical and empirical studies on the relationship between regional growth and innovation activity.The purpose of the review is to classify approaches to analyzing the relationship between knowledge flows and regional growth, stimulated by the diffusion of innovations.Result. The study confirms the basic premise that innovation activity, recorded in calculations through R & D costs, costs of technological innovation and knowledge transfers, are endogenous factors that can explain differences in economic growth.Conclusions are made about the ability to transfer knowledge to reduce inequality in innovation activity among innovative leaders and lagging behind in innovations. There is a connection between geographical proximity and the ability of both explicit and implicit knowledge to spread. The ability to absorb knowledge from exchange participants is damped inversely with the distance between participants, the efficiency of the flow of knowledge depends on the absorptive capacity of the regions.